Thiophostone‐Derived Brønsted Acids in the Organocatalyzed Transfer Hydrogenation of Quinolines: Influence of the P‐Stereogenicity. Issue 1 (24th October 2013) - Ferry, Angélique; Stemper, Jérémy; Marinetti, Angela; Voituriez, Arnaud; Guinchard, Xavier
Abstract: A new approach to Brønsted acid organocatalysis is described and is based on the use of thiophosphonic acids possessing both a chiral backbone and a chiral phosphorus function. The influence of the phosphorus stereochemistry on the enantioselectivity proved to be crucial in the hydrogen transfer hydrogenation of 2‐phenylquinoline with Hantzsch esters. Abstract : The synthesis and catalytic activities of P‐chiral Brønsted acids possessing a thiophostone‐derived skeleton are described. The stereochemical outcome of the test reaction is strongly dependant on the stereochemistry of the phosphorus atom.